2020
DOI: 10.24018/ejbmr.2020.5.1.181
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Islamic Work Ethics, Competencies, Compensation, Work Culture On Job Satisfaction And Employee Performance: The Case Of Four Star Hotels

Abstract: The purpose of this study was to analyze the influence of the Islamic work ethic, competencies, compensation and work culture on the job satisfaction of four-star hotel employees, analyze the influence of the Islamic work ethic, competencies, compensation and work culture on the four-star hotel employees performance, analyze the effect of job satisfaction on four-star hotel employee performance, and analyze the influence of the Islamic work ethic, competencies, compensation and work culture through job satisfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 6 publications
4
37
1
14
Order By: Relevance
“…This study is in line with the findings of previous studies, which state that work ethic variables have a significant relationship with employee performance (Herawati et al, 2020;Raja et al, 2019;Rismawati, 2016;Saban et al, 2020;Susmianto et al, 2018). This finding means that the high work ethic of the employees can improve their performance.…”
Section: Discussionsupporting
confidence: 92%
“…This study is in line with the findings of previous studies, which state that work ethic variables have a significant relationship with employee performance (Herawati et al, 2020;Raja et al, 2019;Rismawati, 2016;Saban et al, 2020;Susmianto et al, 2018). This finding means that the high work ethic of the employees can improve their performance.…”
Section: Discussionsupporting
confidence: 92%
“…Saman A find that compensation has a significant effect on job satisfaction. But it is different from the results of the study which found that compensation had no significant effect on job satisfaction [5][6][7][8][9][10].…”
Section: Effect Of Compensation On Job Satisfactioncontrasting
confidence: 66%
“…Purnama Y, Saban D, Kusumah MSA [6,9,12,25,26] find that job satisfaction has an effect significant positive on employee performance.…”
Section: Job Satisfaction Influences Employee Performancementioning
confidence: 99%
“…Workers who believe in their ability to do a job will encourage the company to motivate employees to work harder, the reciprocal relationship between employees and the company makes employees satisfied (Berlian, 2018). Employees who show their potential according to their knowledge, skills, experience, mastery of attitudes, expertise and skills can affect the employee's job satisfaction (Saban et al, 2020). Thus the next hypothesis proposed is:…”
Section: Hr Competenciesmentioning
confidence: 99%